Proceedings of the first anniversary of the American equal rights association, held at the Church of the Puritans, New York, May 9 and 10, 1867. Phonographic report by H.M. Parkhurst. - American Equal Rights Association; Parkhurst, Henry M. (Henry Martyn), 1825-1908.; Catt, Carrie Chapman, 1859-1947; National American Woman Suffrage Association Collection (Library of Congress); Susan B. Anthony Collection (Library of Congress) (New York, R.J. Johnston, printer, 1867)
This report contains addresses by Elizabeth Cady Stanton, Samuel J. May, C.C. Burleigh, Frances D. Gage, Lucretia Mott, Parker Pillsbury, Ernestine Rose, Henry Ward Beecher, Sojourner Truth, and Charles Lenox Redmond. Some speeches discuss the relationship of woman suffrage to black manhood suffrage and the reasons for enfranchising women. It also includes the constitution of the Equal Rights Association, and correspondence from various individuals.
Also available in digital form on the Library of Congress Web site.
Keywords: Women's rights; Women -- Suffrage -- Congresses; Women -- Suffrage -- United States